Peran Fasilitas Pelayanan Kesehatan Dalam Menangani Situasi Darurat Ditinjau Dari Perspektif Islam - Robbillah Al-Quddus, Viola Maharani; Nisak, Nur Maslikhatun (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2023)
In Islam, health services are public facilities that must be felt and enjoyed by the community. Health care facilities should be evenly distributed to all groups regardless of differences in race, ethnicity, class, or economic level. Of course, in the process of providing health services, there are many problems that make their role in serving the community less able to run as it should. The research method used is SLR (systematic literature review). From the data obtained, there were several cases of rejection of emergency patients and patients who were abandoned due to complicated handling processes and delays in treatment at a number of health care facilities. Through this research, it can be concluded that health service facilities are required to provide fair and appropriate services without prejudice to any conditions or situations, including emergency conditions, that can cause patients to experience disability or loss of life. In addition, the occurrence of cases of refusal of emergency patients by several health care facilities is an act that is very unjust and violates Islamic law.